EFEK APLIKASI BAHAN ORGANIK DAN KONSENTRASI EKSTRAK DAUN KELOR TERHADAP PERTUMBUHAN, HASIL DAN KUALITAS PAKCOY (Brassica rapa L.). - nova ardiansah; Anis Rosyidah; Indiyah Murwani (AGRONISMA, 2022)
This study aims: to determine the effect of the interaction of organic matter application and concentration of Moringa leaf extract on the growth, yield and quality of pakcoy (Brassica rapa L.). The study was conducted from May 2022 to June 2022 at the Green House of the Faculty of Agriculture, Islamic University of Malang, at an altitude of Â± 500 meters above sea level, with a temperature of 23oC - 29oC. Quality analysis was conducted at the Integrated Laboratory of the Faculty of Agriculture, Islamic University of Malang. Factorial Randomized Block Design Research with 2 factors. Factor 1 is organic matter (O) 2 levels, O0 (without organic matter), O1 (with organic matter). Factor 2, namely Moringa leaf extract (K) 4 levels, K0 (without Moringa leaf extract), K1 (2 ml/liter of water), K2 (4 ml/liter of water), K3 (6 ml/liter of water), there were 8 treatment combinations and 3 replications. The results showed that there was no significant interaction with the combination treatment of organic matter and Moringa leaf extract. O1 treatment showed better results on the variables of plant height, number of leaves, leaf area, fresh weight consumption and chlorophyll. Treatment K, had no significant effect on all parameters. Further research needs to be done with higher concentrations of Moringa leaf extract to determine growth, yield and quality. It is necessary to analyze the content of organic matter prior to the study.Key words : Mustard Pakcoy, Organic Matter, Concentration of Moringa Leaf Extract.